Electroactive ordered collagen scaffold and preparation method thereof
By doping carbon nanotubes into the collagen scaffold and constructing a polypyrrole conductive coating to form an electroactive ordered collagen scaffold, the problems of fast degradation speed of existing collagen scaffolds and poor repair of long-segment nerve damage are solved, and the conductivity and degradation performance of the scaffolds are significantly improved, which is suitable for long-term support for nerve repair.
Patent Information
- Application Number
- CN202510076370.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-22
AI Technical Summary
The existing linear collagen stents have a fast degradation and absorption rate, which cannot fully support and protect the nerve regeneration process, and at the same time, the repair effect of long segments or thicker nerve damage is not ideal.
By doping carbon nanotubes (CNTs) in type I collagen and constructing a conductive coating of polypyrrole (PPy) to form an electroactive ordered collagen scaffold, improving the conductivity and degradation performance of the scaffold.
This scaffold not only provides spatial support and topographic guidance at the physical level, but also promotes electrical signaling between nerve cells through conductivity, significantly improving the extension of neuronal axons and the degradation performance of collagen scaffolds, which is suitable for long-term neural repair.
Smart Images

Figure CN119857179A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biological tissue engineering materials, and more particularly to an electrically active ordered collagen scaffold and a preparation method thereof. Background Art
[0002] Spinal cord injury (SCI) is a serious traumatic spinal disease with a poor prognosis. According to epidemiological statistics, the incidence of SCI is increasing year by year worldwide, and it has a high disability rate, many complications, and expensive treatment costs, which brings serious physical, psychological and economic burdens to patients and also creates tremendous pressure on society. In recent years, the treatment of SCI has made some progress, but still only <1% of patients can fully recover their neurological function. How to promote the repair of neurological function after SCI has become a major problem in clinical and scientific research.
[0003] The application of biological tissue engineering materials to treat spinal cord injury is considered to be a promising treatment method. Among them, linear collagen scaffold (LOCS) is a linear, ordered scaffold material prepared using collagen that can guide nerve regeneration. It has the functions of inhibiting glial scar formation, providing a microenvironment for neuronal survival and growth, and guiding axons to grow and extend along linear collagen fibers. Previous research results also showed that LOCS scaffolds can promote nerve regeneration and motor function recovery in rat and dog spinal cord complete transection models. However, its degradation and absorption rate is relatively fast, which is not enough to fully support and protect the entire nerve regeneration process. Moreover, the nerve scaffold with collagen as the main component alone is not ideal for the repair of long segments, especially thicker nerve injuries. To make up for this defect, researchers have adopted various strategies, such as improving the mechanical and degradation properties of collagen scaffolds through cross-linking with chemical reagents such as glutaraldehyde, genipin, EDC / NHS, or some scholars have used natural linear polysaccharide heparin sulfate to combine with collagen to simulate the neural basement membrane, while improving the mechanical strength of collagen, which can maintain a certain spatial structure for nerve regeneration. Or there are also ways to combine collagen with chitosan or collagen with synthetic polymers. However, most of these methods are limited to regulating and improving the morphology or mechanical, degradation and other properties of collagen scaffolds, and the role of the scaffold is more of a physical spatial support or terrain guidance role. In neural tissue, the functionality of neurons is related to the transmission of electrical signals, and the signal transmission of nerve axons also relies on electrical signals. Therefore, conductivity can be used as one of the factors for regulating neural tissue repair by tissue engineering collagen scaffolds.
[0004] Based on this, it is an urgent problem for technical personnel in this field to develop an integrated solution that can improve the degradation performance of collagen scaffolds while giving them conductive properties, providing long-term spatial support, topographic guidance and electrophysiological microenvironment for neural tissue or cells. Summary of the invention
[0005] In view of this, the present invention provides an electroactive ordered collagen scaffold and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing an electroactive ordered collagen scaffold comprises the following steps:
[0008] S1: Dissolve type I collagen (Co l) in acetic acid solution, add carbon nanotube conductive powder (CNTs) while stirring with a magnetic stirrer at room temperature, stir for 20-30 minutes, insert an ultrasonic probe into the mixed solution in an ice-water mixing bath, and continue to mix the CNTs thoroughly;
[0009] S2: The CNTs@Co l mixed solution was vacuumed under negative pressure and placed at 4°C for 12-16 hours to obtain a gel suspension;
[0010] S3: inject the gel suspension into a molding container, immerse it in liquid nitrogen cryogen along the axial direction for 30-60 minutes, then transfer it to -80℃ for 4-5 hours, and then transfer it to a freeze dryer for freeze drying for 18-24 hours to obtain a dry and molded CNTs@Co l scaffold material;
[0011] S4: In situ oxidative polymerization to construct a polypyrrole (PPy) coating. First, place the CNTs@Co l scaffold in a centrifuge tube filled with 0.5M ferric chloride solution. After soaking for 30-60 minutes, take out the CNTs@Co l scaffold and place it in a culture dish filled with pyrrole solution to ensure that the scaffold is completely immersed in the pyrrole solution. React at 4°C for 12-16 hours to allow pyrrole monomers to oxidatively polymerize on the scaffold to form a PPy coating.
[0012] S5: After the reaction is completed, the obtained CNTs@Co l / PPy composite scaffold is repeatedly washed with anhydrous ethanol and deionized water to remove the unreacted pyrrole monomer and ferric chloride, and then dried in a vacuum drying oven to obtain an electroactive collagen scaffold.
[0013] The type I collagen in step S1 comes from bovine Achilles tendon, the concentration of the acetic acid solution is 0.5 mol / L, and the dissolved concentration of type I collagen in acetic acid is 10-20 mg / ml.
[0014] In step S1, the concentration of the carbon nanotube powder in the acetic acid solution is 0.5-2 mg / ml, and the outer diameter of the carbon nanotube powder is 8-15 nanometers and the length is 50 micrometers.
[0015] In step S1, the speed of the magnetic stirrer is 800 r / min, the working parameters of the ultrasonic probe are 21-25 KHz, 950 W, ultrasound is on for 2 seconds, off for 1 second, and the ultrasound time is 40-60 minutes.
[0016] The parameters of negative pressure vacuuming in step S2 are -0.15 to -0.05 MPa, 35-40° C., and the vacuuming time is 40-60 min.
[0017] In step S3, the shaping container is a silicone tube with an inner diameter of 3 mm and a length of 10 cm, and both ends of the silicone tube are sealed by clamping lead wire.
[0018] The setting parameters of the freeze dryer in step S3 are -80°C and 1 mTorr.
[0019] The dried and formed CNTs@Co l scaffold in step S3 is cut into segments of 1.5-2 cm.
[0020] The concentration of the pyrrole solution in step S4 is 0.3-0.7 mol / L.
[0021] The parameters of the vacuum drying oven in step S5 are -0.15 to -0.05 MPa, 35-40° C., and the drying time is 24-48 hours.
[0022] Another object of the present invention is to provide an electrically active ordered collagen scaffold prepared by the above preparation method.
[0023] Another object of the present invention is to provide the use of the electroactive ordered collagen scaffold prepared by the above preparation method in the preparation of spinal cord injury repair materials.
[0024] Beneficial effects:
[0025] The electrically active ordered collagen scaffold of the present invention is constructed by gradient condensation after internal doping of carbon nanotubes (CNTs) and in-situ polymerization of a polypyrrole (PPy) conductive coating to have an ordered collagen scaffold with conductive properties in both the inner and outer structures. The preparation method is simple, and the good biocompatibility of the scaffold can be ensured by adjusting the ratio of CNTs and PPy.
[0026] The stent of the present invention not only plays a role in topographic guidance, but also has the conductive property to promote the conduction of electrical signals between nerve cells and promote the growth and development of nerve cells. In in vitro cell experiments, the stent showed a promoting effect on the extension of neuronal axons, and the promoting effect of the inner and outer double conductive structure was better than that of the inner single conductive structure, which shows that the inner and outer double conductive structure of the present invention is more beneficial to the growth of nerve cells.
[0027] Due to the protective effect of the PPy coating, the anti-absorption and degradation properties of the stent of the present invention are significantly improved, which can better match the time requirement of nerve repair.
[0028] In this way, the electroactive ordered collagen scaffold can provide a convenient environment for nerve repair from multiple angles, thereby accelerating the repair of nerve damage. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0030] Figure 1 The general image of the stent made of silicone mold (3 mm in diameter, 15 mm in length) and the scanning electron microscope observation images of the CNTs@Co l / PPy stents of Example 1 and Example 2;
[0031] Figure 2 The test results of the electrical conductivity of four scaffolds are shown in Figure 1. Control Example 1: Co l group; Control Example 2: CNTs@Co l group; Example 1: CNTs@Co l / PPy-1 group; Example 2: CNTs@Co l / PPy-2 group;
[0032] Figure 3 The in vitro degradation time curves of four scaffolds are shown in Table 1. Control Example 1: Co l group; Control Example 2: CNTs@Co l group; Example 1: CNTs@Co l / PPy-1 group; Example 2: CNTs@Co l / PPy-2 group;
[0033] Figure 4The β-3-tubu lin immunofluorescence staining images of neurons cultured on the surfaces of four scaffolds at 7 days and the analysis images of neuronal axon length (n=3; *P<0.05, **P<0.01, ***P<0.001); wherein, a is the fluorescence staining image of the surface neurons of the Col group in control example 1, b is the fluorescence staining image of the surface neurons of the CNTs@Col group in control example 2, c is the fluorescence staining image of the surface neurons of the CNTs@Col / PPy-1 group in example 1, d is the fluorescence staining image of the surface neurons of the CNTs@Col / PPy-2 group in example 2, and e is the statistics of the average neurite length of neurons grown on the surface of each group of materials (in e, control example 1 is the Col group, control example 2 is the CNTs@Col group, example 1 is the CNTs@Col / PPy-1 group, and example 2 is the CNTs@Col / PPy-2 group). DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] S1: Dissolve type I collagen from bovine Achilles tendon in 10 ml of 0.5M acetic acid solution at a concentration of 10 mg / ml, and add carbon nanotube conductive powder while stirring at 800 r / min using a magnetic stirrer at room temperature. The concentration of carbon nanotube powder added to the acetic acid solution is 0.5 mg / ml, the outer diameter is 8-15 nanometers, and the length is 50 microns. After stirring for 20 minutes, insert the ultrasonic probe into the mixed solution in an ice-water mixing bath. The working parameters of the ultrasonic probe are 21KHz, 950W, ultrasound on for 2s, off for 1s, and ultrasound time for 60 minutes, and continue to mix the CNTs thoroughly;
[0037] S2: The CNTs@Co l mixed solution was vacuumed at -0.15~-0.05MPa, 35-40℃ for 40min, and then placed at 4℃ for 12h to obtain a gel suspension;
[0038] S3: The gel suspension was injected into a silicone tube-shaped container with an inner diameter of 3 mm and a length of 10 cm. The two ends of the sealed silicone tube were clamped with lead wires, and the container was immersed in liquid nitrogen cryogen along the axial direction for 30 min. The container was then transferred to -80 °C for freezing for 5 h, and then transferred to a freeze dryer for freeze drying at -80 °C and 1 mTorr for 24 h to obtain a dried and molded CNTs@Co l scaffold material. The CNTs@Co l scaffold was then cut into 1.5-2 cm segments.
[0039] S4: In situ oxidative polymerization to construct a polypyrrole (PPy) coating. First, place the CNTs@Co l scaffold in a centrifuge tube filled with 0.3M ferric chloride solution. After soaking for 30 minutes, take out the CNTs@Co l scaffold and place it in a culture dish filled with 0.3 mol / L pyrrole solution to ensure that the scaffold is completely immersed in the pyrrole solution. The reaction is carried out at 4°C for 16 hours to allow the pyrrole monomer to oxidatively polymerize on the scaffold to form a PPy coating.
[0040] S5: After the reaction is completed, the obtained CNTs@Co l / PPy composite scaffold is repeatedly washed with anhydrous ethanol and deionized water to remove the unreacted pyrrole monomer and ferric chloride, and then dried in a vacuum drying oven at -0.15 to -0.05 MPa and 35-40°C for 48 hours to obtain an electroactive collagen scaffold.
[0041] Example 2
[0042] S1: Dissolve type I collagen from bovine Achilles tendon in 10 ml of 0.5M acetic acid solution at a concentration of 20 mg / ml, and add carbon nanotube conductive powder while stirring at 800 r / min using a magnetic stirrer at room temperature. The concentration of carbon nanotube powder after adding acetic acid solution is 2 mg / ml, the outer diameter is 8-15 nanometers, and the length is 50 microns. After stirring for 30 minutes, insert the ultrasonic probe into the mixed solution in an ice-water mixing bath. The working parameters of the ultrasonic probe are 25KHz, 950W, ultrasound on for 2s, off for 1s, and ultrasound time for 40 minutes, and continue to mix the CNTs thoroughly;
[0043] S2: The CNTs@Co l mixed solution was vacuumed at -0.15~-0.05MPa, 35-40℃ for 60min, and then placed at 4℃ for 16h to obtain a gel suspension;
[0044] S3: The gel suspension was injected into a silicone tube-shaped container with an inner diameter of 3 mm and a length of 10 cm. The two ends of the sealed silicone tube were clamped with lead wires, and the tube was immersed in liquid nitrogen cryogen along the axial direction for 60 min. Then, the tube was transferred to -80 °C for freezing for 4 h, and then transferred to a freeze dryer for freeze drying at -80 °C and 1 mTorr for 18 h to obtain a dry and molded CNTs@Co l scaffold material. The CNTs@Co l scaffold was then cut into 1.5-2 cm segments.
[0045] S4: In situ oxidative polymerization to construct a polypyrrole (PPy) coating. First, place the CNTs@Co l scaffold in a centrifuge tube filled with 0.5M ferric chloride solution. After soaking for 60 minutes, take out the CNTs@Co l scaffold and place it in a culture dish filled with 0.7 mol / L pyrrole solution to ensure that the scaffold is completely immersed in the pyrrole solution. The reaction is carried out at 4°C for 12 hours to allow the pyrrole monomer to oxidatively polymerize on the scaffold to form a PPy coating.
[0046] S5: After the reaction is completed, the obtained CNTs@Co l / PPy composite scaffold is repeatedly washed with anhydrous ethanol and deionized water to remove the unreacted pyrrole monomer and ferric chloride, and then dried in a vacuum drying oven at -0.15 to -0.05 MPa and 35-40°C for 24 hours to obtain an electroactive collagen scaffold.
[0047] Comparative Example 1
[0048] S1: Dissolve type I collagen from bovine Achilles tendon at a concentration of 20 mg / ml in 10 ml of 0.5 M acetic acid solution and stir at 800 r / min for 30 min using a magnetic stirrer at room temperature;
[0049] S2: The Col solution was evacuated at -0.15 to -0.05 MPa and 35-40°C for 60 min, and then placed at 4°C for 16 h to obtain a gel suspension;
[0050] S3: Inject the gel suspension into a silicone tube molding container with an inner diameter of 3mm and a length of 10cm. Clamp the two ends of the sealed silicone tube with lead wire, immerse it axially in liquid nitrogen refrigerant for 60min, then transfer it to -80℃ and freeze it for 4h. Then move it into a freeze dryer and freeze-dry it at -80℃ and 1mTorr for 18h to obtain the dried and formed Col stent material. Then cut the Col stent into 1.5-2cm segments.
[0051] Comparative Example 2
[0052] S1: Dissolve type I collagen from bovine Achilles tendon in 10 ml of 0.5M acetic acid solution at a concentration of 20 mg / ml, and add carbon nanotube conductive powder while stirring at 800 r / min using a magnetic stirrer at room temperature. The concentration of carbon nanotube powder after adding acetic acid solution is 2 mg / ml, the outer diameter is 8-15 nanometers, and the length is 50 microns. After stirring for 30 minutes, insert the ultrasonic probe into the mixed solution in an ice-water mixing bath. The working parameters of the ultrasonic probe are 25KHz, 950W, ultrasound on for 2s, off for 1s, and ultrasound time for 40 minutes, and continue to mix the CNTs thoroughly;
[0053] S2: The CNTs@Co l mixed solution was vacuumed at -0.15~-0.05MPa, 35-40℃ for 60min, and then placed at 4℃ for 16h to obtain a gel suspension;
[0054] S3: Inject the gel suspension into a silicone tube molding container with an inner diameter of 3mm and a length of 10cm. Clamp the two ends of the sealed silicone tube with lead wire, immerse it axially in liquid nitrogen refrigerant for 60min, then transfer it to -80℃ and freeze it for 4h. Then move it into a freeze dryer and freeze-dry it at -80℃ and 1mTorr for 18h to obtain the dried and formed CNTs@Co l scaffold material. Then cut the CNTs@Co l scaffold into 1.5-2cm segments.
[0055] Experimental example
[0056] The electroactive ordered scaffolds prepared in Example 1 and Example 2 were used as observation objects. Scanning electron microscopy showed that the fibers inside the scaffolds were loose and porous, and orderly arranged, which can provide a spatial structure and topographic guidance for the growth of nerve axons. At the same time, due to the high collagen concentration, CNTs incorporation and PPy modification concentration selected in Example 2, the fiber structure was denser than that in Example 1 (see Appendix Figure 1 ).
[0057] Taking Control Example 1, Control Example 2, Example 1 and Example 2 as experimental objects, we used RST-8 four-pin probe to test the conductivity of three kinds of brackets. Three samples were taken from each group of brackets, and the test results were averaged. The experimental results show that the conductivity of Control Example 1: Co l bracket is 2.79×10 -8S / m, no conductivity; Control Example 2: The conductivity of CNTs@Co l scaffold is 0.189S / m, and the incorporation of CNTs improves the conductivity; Example 1: CNTs@Co l / PPy-1 scaffold, the conductivity is 0.385S / m, good conductivity; Example 2: CNTs@Co l / PPy-2 scaffold, the conductivity is 0.61S / m, and the conductivity is further enhanced. This shows that the dual conductive strategy of internal doping of CNTs and in-situ construction of PPy coating on the surface of the present invention is more conducive to the enhancement of material conductivity (see Appendix Figure 2 ).
[0058] Taking Control Example 1, Control Example 2, Example 1 and Example 2 as experimental objects, we sterilized the 4 groups of 3mm diameter and 1.5cm long stents by cobalt 60 irradiation at a dose of 25kGy. The in vitro degradation time observation period was 20 weeks (w), and the test was performed every 2w. Three parallel samples were set for each group of samples at each time point. The initial mass of each stent of the three groups of samples was recorded, recorded as W0, and the three groups of sterilized samples were placed in 15ml centrifuge tubes containing 10ml SBF simulated body fluid under sterile conditions. The SBF simulated body fluid was changed once a week under sterile conditions. At each observation time point, the three parallel samples of the three groups of stents were taken out, washed with deionized water, and dried overnight. The mass of each stent after drying was recorded as W. The mass loss rate was calculated and the in vitro degradation curve was drawn. The calculation formula is: (W0-W) / W0×100%. The mass loss rate of the three parallel samples of the three groups of stents at each time point was averaged. From the in vitro degradation curve, it can be seen that control example 1: the Col group was completely degraded at 10 weeks; control example 2: the CNTs@Co l group was completely degraded at 12 weeks, which shows that the doping of CNTs has prolonged the degradation time of the collagen scaffold to a certain extent; Example 1: the degradation time of the CNTs@Co l / PPy-1 group was extended to 14 weeks, which shows that the construction of the PPy surface coating has a protective effect on collagen, which further prolongs the degradation time of the collagen scaffold; Example 2: the degradation time of the CNTs@Co l / PPy-2 group was extended to 16 weeks due to the high concentrations of CNTs incorporation and PPy modification. For nerve repair, a long repair cycle is required. The longer maintenance of the CNTs@Co l / PPy scaffold will help it to play a long-term role in spatial support and terrain guidance (see Appendix Figure 3 ).
[0059] Using Control Example 1, Control Example 2, Example 1 and Example 2 as experimental objects, we cut each group of scaffolds into slices with a thickness of 1 mm, sterilized them by Cobalt 60 irradiation, and then inoculated neurons onto the surface of each group of collagen scaffold slices for co-culture experiments. After 7 days of culture, we performed β-3-tubulin immunofluorescence staining to observe the growth of neurons. The results showed that, except for the control example 1: Col group, where the neuron axon extension was poor, the neurons in the other three groups grew well. In the control example 2: CNTs@Col group, the axon extension of neurons was improved due to the conductive properties of CNTs incorporated; and in the example 1: CNTs@Col / PPy-1 group and the example 2: CNTs@Col / PPy-2 group, this improvement was more obvious, and the neuron axons were further extended. This benefited from the construction of the dual conductive strategy. The PPy surface conductive coating made the electrical signal transmission between the neuron cells growing on the surface of the conductive coating closer, and because the conductivity of the example 2: CNTs@Col / PPy-2 group was stronger, the axon extension of neurons was significantly improved, which was more conducive to the function of neurons. This shows the application prospect of this scaffold in nerve repair (see Appendix). Figure 4 ).
[0060] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0061] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing an electroactive ordered collagen scaffold, characterized in that: The following steps are involved: S1: Dissolve type I collagen (Col) in acetic acid solution, add carbon nanotube conductive powder (CNTs) under stirring, stir for 20-30 minutes, and then mix the CNTs thoroughly by ultrasound in an ice-water mixing bath; S2: The CNTs@Col mixed solution was vacuumed under negative pressure and placed at 4°C for 12-16 hours to obtain a gel suspension; S3: inject the gel suspension into a molding container, immerse it in liquid nitrogen cryogen along the axial direction for 30-60 minutes, then transfer it to -80℃ for 4-5 hours, and then transfer it to a freeze dryer for freeze drying for 18-24 hours to obtain a dry and molded CNTs@Col scaffold material; S4: In situ oxidative polymerization to construct a polypyrrole (PPy) coating. First, place the CNTs@Col scaffold in a centrifuge tube containing a 0.5M ferric chloride solution. After soaking for 30-60 minutes, take out the CNTs@Col scaffold and place it in a culture dish containing a pyrrole solution to ensure that the scaffold is completely immersed in the pyrrole solution. The reaction is carried out at 4°C for 12-16 hours to allow the pyrrole monomer to oxidatively polymerize on the scaffold to form a PPy coating. S5: After the reaction is completed, the obtained CNTs@Col / PPy composite scaffold is repeatedly washed with anhydrous ethanol and deionized water to remove the unreacted pyrrole monomer and ferric chloride, and then dried in a vacuum drying oven to obtain an electroactive collagen scaffold.
2. The preparation method according to claim 1, characterized in that: The type I collagen in S1 comes from bovine Achilles tendon, the concentration of the acetic acid solution is 0.5 mol / L, and the concentration of type I collagen in acetic acid is 10-20 mg / ml; the concentration of carbon nanotube powder in acetic acid solution is 0.5-2 mg / ml, and the outer diameter of the carbon nanotube powder is 8-15 nanometers and the length is 50 microns.
3. The preparation method according to claim 1, characterized in that: In S1, the stirring rate is 800 r / min, the ultrasonic parameters are 21-25 KHz, 950 W, the ultrasound is on for 2 s, off for 1 s, and the ultrasonic time is 40-60 min.
4. The preparation method according to claim 1, characterized in that: The negative pressure vacuuming parameters in S2 are -0.15~-0.05MPa, 35-40℃, and the vacuuming time is 40-60min.
5. The preparation method according to claim 1, characterized in that: The shaping container in S3 is a silicone tube with an inner diameter of 3 mm and a length of 10 cm, and both ends of the silicone tube are sealed by clamping lead wire.
6. The preparation method according to claim 1, characterized in that: The setting parameters of the freeze dryer in S3 were -80°C and 1 mTorr; the CNTs@Col scaffolds dried and formed in S3 were cut into segments of 1.5-2 cm.
7. The preparation method according to claim 1, characterized in that: The concentration of pyrrole solution in S4 is 0.3-0.7 mol / L.
8. The preparation method according to claim 1, characterized in that: The parameters of the vacuum drying oven in S5 are -0.15~-0.05MPa, 35-40℃, and the drying time is 24-48h.
9. The electroactive ordered collagen scaffold prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the electroactive ordered collagen scaffold prepared by the preparation method according to any one of claims 1 to 8 in preparing spinal cord injury repair materials.